Space men [videorecording (DVD)] - Pollak, Amanda; Ryan, Craig, 1953-; Hollings, Ken; Bilger, Burkhard; Rundquist, Peter (WGBY DVD Collection, 2016)
On an August morning in 1960, Air Force Captain Joseph Kittinger stepped out of a helium balloon twenty miles above Earth, hurtling down at over 400 miles per hour. The little-known story of the men whose scientific experiments laid critical groundwork for NASA's manned space program, a decade before President Kennedy committed the nation to sending a man to the moon.